Analisis Dampak Muhadarah Terhadap Pembentukan Karakter Religius Santri di Madrasah Tsanawiyah di Pondok Pesantren Syekh Ibrahim Kumpulan Kabupaten Pasaman - Febriyanti, Elsa; Abdul Karim, Hamdi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research is motivated by the problems encountered, such as there are still a number of students who neglect their religious obligations such as not performing prayers and not being respectful in carrying out religious activities such as muhadarah which is carried out in the Syekh Ibrahim Kumpulan Islamic boarding school environment, there are several students who do not appear, even though they have appointed on the day before appearing, this is due to lack of self-confidence and preparation. Violations of Islamic boarding school rules such as skipping school, leaving the boarding school without permission, often being late, fighting. The aim to be achieved in this research is to determine the Analysis of Muhadarah Activities on the Formation of the Religious Character of Madrasah Tsanawiyah Students at the Syekh Ibrahim Islamic Boarding School in Pasaman Regency. This research is qualitative research, researchers use descriptive type research. The data collection techniques used to collect data in this research are: observation, interviews, documentation. The data analysis that researchers use in this research is data reduction, data presentation, drawing conclusions. To test the validity of the data, researchers used Source Triangulation and Technical Triangulation. The results of the research analysis of Muhadarah activities in forming the religious character of santri at the Madrasah Tsanawiyah at the Syekh Ibrahim Pesantren Pesantren, Pasaman Regency, Muhadarah activities which are routinely carried out 4 times a week, namely Tuesday, Wednesday, Thursday and Saturday can have a positive impact on the santri. This is marked by a change in the attitude of students who obey the rules of the Islamic boarding school. Like carrying out midday prayers in congregation, this can increase the faith and devotion of students. By maintaining prayer, it will reflect the good morals and character of the students. The results of the implementation of muhadarah activities towards the formation of the religious character of students at the Sykeh Ibrahim Islamic boarding school, Pasaman Regency, are in obedience, namely increased awareness of students to carry out midday prayers on time and carried out in congregation, students are diligent in reciting the Al-Qur'an to improve the quality of memorization, students close intimate and obedient to Islamic boarding school rules, in the form of tolerance, namely students respecting friends who appear by listening carefully, in the form of harmony, namely students always respecting each other, teachers and the community, this can minimize the occurrence of conflicts between students.